2012
DOI: 10.1371/journal.ppat.1002736
|View full text |Cite
|
Sign up to set email alerts
|

DNase Sda1 Allows Invasive M1T1 Group A Streptococcus to Prevent TLR9-Dependent Recognition

Abstract: Group A Streptococcus (GAS) has developed a broad arsenal of virulence factors that serve to circumvent host defense mechanisms. The virulence factor DNase Sda1 of the hyperinvasive M1T1 GAS clone degrades DNA-based neutrophil extracellular traps allowing GAS to escape extracellular killing. TLR9 is activated by unmethylated CpG-rich bacterial DNA and enhances innate immune resistance. We hypothesized that Sda1 degradation of bacterial DNA could alter TLR9-mediated recognition of GAS by host innate immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 42 publications
0
63
0
3
Order By: Relevance
“…Bacterial strains that express DNase as virulence factor were shown to break down NETs and disseminate more efficiently (28)(29)(30). Furthermore, it was recently shown that NETs, which are formed in the vasculature, efficiently trapped bacteria in the bloodstream, and in vivo removal of NETs by administration of recombinant DNase promoted hypersusceptibility to sepsis (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains that express DNase as virulence factor were shown to break down NETs and disseminate more efficiently (28)(29)(30). Furthermore, it was recently shown that NETs, which are formed in the vasculature, efficiently trapped bacteria in the bloodstream, and in vivo removal of NETs by administration of recombinant DNase promoted hypersusceptibility to sepsis (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that formation of NETs impaired bacterial survival (14,30,(38)(39)(40). However, others showed entrapment of bacteria or Candida albicans by NETs without killing (41).…”
Section: Discussionmentioning
confidence: 99%
“…Bu araştırmanın sonucunda, klinik görü-nüm ile emm tipleri veya virülans faktörleri arasında bir korelasyon olmadığı, buna karşın konak immün yanıtının belirleyici olduğu vurgulanmıştır 28 . Uchiyama ve arkadaşları 29 ise, GAS ile ilişkili farklı virülans faktörlerini ve bunların immün sistemle olan ilişkilerini araş-tırmışlardır. Bu çalışmada, yakın zamanda keşfedilen bir diğer GAS virülans faktörü olan streptodornaz (Sda1)'ın, doğal immün yanıtın bir parçası olan Toll benzeri reseptör-9 (TLR-9) üzerine olan etkisini tespit etmek için, deneysel hayvan modeli oluşturulmuştur.…”
Section: Discussionunclassified
“…Bu çalışmada, yakın zamanda keşfedilen bir diğer GAS virülans faktörü olan streptodornaz (Sda1)'ın, doğal immün yanıtın bir parçası olan Toll benzeri reseptör-9 (TLR-9) üzerine olan etkisini tespit etmek için, deneysel hayvan modeli oluşturulmuştur. Sonuç olarak, Sda1'in TLR-9 aracılı immün yanıtı baskıladığı ve bu sayede GAS'ın, makrofajların bakterisidal etkilerinden kaçabildiği belirlenmiştir 29 . Ne var ki, bütün bu araştır-malara karşın, GAS'a karşı gelişen immün yanıtın bireyler arasında neden bu kadar farklı olduğu net olarak cevaplanamamıştır.…”
Section: Discussionunclassified
“…13 ETs are also likely to alert the immune system by activating DNA receptors, such as TLR-9, which aid in immune cell recruitment and the mounting of an acquired immune response or in reducing inflammation. 32 Successful microbial pathogens have in turn evolved complex and efficient methods to overcome immune mechanisms. Multiple virulence factors that counteract ETs have been identified.…”
Section: Discussionmentioning
confidence: 99%